2013
DOI: 10.1155/2013/148725
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Type I Interferon Signaling Rescues Lymphocytes from Oxidative Stress, Exhaustion, and Apoptosis in a Streptozotocin-Induced Mouse Model of Type I Diabetes

Abstract: Elevated levels of type I interferon (IFN) during type 1 diabetes mellitus (T1D) are associated with a defective immune response. In the present study, we investigated whether blocking type I IFN signaling during streptozotocin- (STZ-) induced T1D in mice improves lymphocyte proliferation and escape from continuous apoptosis. Three groups of mice were examined: diabetic mice, type I IFN signaling-incompetent diabetic mice, and control nondiabetic mice. We first found that diabetes induction was accompanied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…We recently investigated the effect of STZ-induced immunosuppression in an animal model [36]. First, pancreatic sections from both STZ-treated and naive mice were stained with H&E and examined by light microscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently investigated the effect of STZ-induced immunosuppression in an animal model [36]. First, pancreatic sections from both STZ-treated and naive mice were stained with H&E and examined by light microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Forty Swiss Webster mice were assigned to three experimental groups: group 1, the non-diabetic control group (n=10), was injected with vehicle alone (0.01 M citrate buffer, pH 4.5); group 2, the diabetic group (n=15), was rendered diabetic by intraperitoneal injection of a single dose of STZ (60 mg per kilogram of body weight) in 0.01 M citrate buffer (pH 4.5); group 3 (n=15) was rendered diabetic using the same procedure as in group 2 but was also injected intraperitoneally, one month after diabetes induction, with an anti-IFN (alpha, beta and omega) receptor 1 (IFNAR1) antibody at a dose of 10 mg per kilogram of body weight daily for up to 20 days [36,37]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wang et al showed that the up regulation of IFNβ expression in dendritic cells promoted antigen presentation but compromised T cell priming 7 . Another study showed that elevated levels of type I IFNs during type 1 diabetes triggered lymphocyte exhaustion and disabled lymphocyte-mediated immune responses 8 . In a tumour-bearing mouse model, IFNα augmented programmed cell death 1 (PD1) expression on antigenspecific CD8 + T cells and thus significantly inhibited T cell-mediated immunity 9 .…”
mentioning
confidence: 99%
“…Samples were analyzed by flow cytometry using a FACS caliber flow cytometer (BD immune cytometry systems, San Jose, CA). The FL2 red fluorescence channel was assessed on a linear scale, and the percentage of cells undergoing cell death was determined as the percentage of hypodiploid cells (sub G0/G1 peak) [34]. …”
mentioning
confidence: 99%